The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fped.2022.795596
|View full text |Cite
|
Sign up to set email alerts
|

Overweight/Obesity in Childhood and the Risk of Early Puberty: A Systematic Review and Meta-Analysis

Abstract: PurposeTo determine the relationship between childhood overweight/obesity and early puberty in both boys and girls. Specifically, this is the first time to conduct a meta-analysis of the relationship between childhood overweight/obesity and early puberty in boys.MethodsRelevant studies were identified from PubMed, Web of Science, and EMBASE searches. The exposure of interest was overweight/obesity in childhood. Childhood was defined internationally as the age range of 0–18 years. The overall risk estimates wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
(47 reference statements)
1
9
0
1
Order By: Relevance
“…Children with obesity experience accelerated growth [52] and, particularly in girls, earlier puberty [53, 54]. A meta‐analysis and systematic review showed that girls with overweight and obesity are at increased risk of early puberty (4.67‐fold and 2.22‐fold, respectively) compared with those with normal weight [55]. This relationship was not statistically significant among boys.…”
Section: Discussionmentioning
confidence: 99%
“…Children with obesity experience accelerated growth [52] and, particularly in girls, earlier puberty [53, 54]. A meta‐analysis and systematic review showed that girls with overweight and obesity are at increased risk of early puberty (4.67‐fold and 2.22‐fold, respectively) compared with those with normal weight [55]. This relationship was not statistically significant among boys.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of obesity have produced more mixed results, with substantial variation in findings by developmental stage, sample characteristics (e.g., ADHD symptoms, pubertal stage, IQ), and task type (e.g., real vs. hypothetical) 17,25 . Pubertal status may be a particularly important confounder to consider given the impact of puberty on body weight, 26 eating behavior, 27 and brain development 28 …”
Section: Introductionmentioning
confidence: 99%
“…23,24 Studies of obesity have produced more mixed results, with substantial variation in findings by developmental stage, sample characteristics (e.g., ADHD symptoms, pubertal stage, IQ), and task type (e.g., real vs. hypothetical). 17,25 Pubertal status may be a particularly important confounder to consider given the impact of puberty on body weight, 26 eating behavior, 27 and brain development. 28 As far as we are aware, no published studies have examined whether experiential DD using a salient, concrete non-food reward varies by body weight in either TD children or children with ADHD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is associated with earlier pubertal timing in girls and possibly boys. 5 The average body mass index (BMI) of each subgroup throughout the study was not reported, but Kubo et al 3 addressed obesity as a potential confounder by performing a sensitivity analysis including only those individuals who had a prepubertal BMI between the 5th and 85th percentiles. The differences in pubertal timing among subgroups persisted after removing individuals with a BMI that fell outside…”
mentioning
confidence: 99%